Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1136/rmdopen-2021-001726
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor: a potential biomarker for chronic low back pain in patients with Modic changes

Abstract: BackgroundLow back pain (LBP) is a leading cause of disability worldwide, but the aetiology remains poorly understood. Finding relevant biomarkers may lead to better understanding of disease mechanisms. Patients with vertebral endplate bone marrow lesions visualised on MRI as Modic changes (MCs) have been proposed as a distinct LBP phenotype, and inflammatory mediators may be involved in the development of MCs.ObjectivesTo identify possible serum biomarkers for LBP in patients with MCs.MethodsIn this case cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…7,8 Intervertebral disc degeneration (IVDD), Modic changes, and fatty infiltration in the paraspinal muscles were considered as the possible origins of LBP. [9][10][11][12][13][14][15][16][17] However, patients with LBP and asymptomatic subjects did not differ in prevalence of IVDD and Modic changes. 18,19 Even though parasinal muscles are the main stabilizers of the lumber spine, most of the previous studies did not focus on paraspinal muscles.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…7,8 Intervertebral disc degeneration (IVDD), Modic changes, and fatty infiltration in the paraspinal muscles were considered as the possible origins of LBP. [9][10][11][12][13][14][15][16][17] However, patients with LBP and asymptomatic subjects did not differ in prevalence of IVDD and Modic changes. 18,19 Even though parasinal muscles are the main stabilizers of the lumber spine, most of the previous studies did not focus on paraspinal muscles.…”
mentioning
confidence: 79%
“…Spine studies have focused on IVDD and Modic changes rather than paraspinal muscles until the recent decade. [12][13][14][15][16][17][18][19]21 It has been reported that multifidus could be the source of LBP in symptomatic subjects. 29 However, studies comparing the symptomatic and matched asymptomatic subjects were rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic inflammatory mediators from patients with vertebral endplate bone marrow lesions visualized on MRI as Modic changes (MCs) were analyzed. The results suggest MIF was strongly expressed in LBP patients with MC 111 . In a similar study, Karppinen et al screened diverse panels of biomarkers in serum of CLBP patients with MCs compared to a matched pain‐free control group 112 .…”
Section: Systemic Biomarkersmentioning
confidence: 94%